Respon terhadap Otentisitas: Tanggapan Wisatawan Asing terhadap Unsur-unsur Budaya dalam Tiga Hotel Internasional di Bali - I Putu Prasista Bestari; I. G.A. Oka Suryawardani; Agung Suryawan Wiranatha (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
This article examines how foreign tourists respond to authentic elements of Balinese culture displayed by hoteliers in Bali. It takes three international hotels as the object of study, namely the Nusa Dua Beach Resort and Spa Hotel, W Hotel Seminyak, and Four Seasons Resort in Ubud. These three hotels were chosen because they are international hotels located in three different tourist destinations, but all offer elements of Balinese culture as part of their services. The article discusses the problem of how tourists respond to elements of Balinese culture, especially architecture, food, art-culture and hospitality. This is qualitative research that draws on data collected through the technique of netnography in the form of tourist comments posted on Tripadvisor about services in the hotel where they stayed. Data were analyzed with response theory and interpretive content analysis theory. Analysis shows that tourists are attracted to authentic elements of Balinese culture. The article recommends that international hotels explicitly display elements of Balinese culture to support the image of Bali as a cultural tourism destination.Keywords: Balinese culture, architecture, Balinese food, netnography, hospitality